1998
DOI: 10.1007/s004250050268
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of decreased triose phosphate/phosphate translocator activity by accelerated starch turnover and glucose transport in transgenic tobacco

Abstract: Tobacco (Nicotiana tabacum L.) plants were transformed with an antisense construct of the chloroplast triose phosphate/phosphate translocator (TPT). Three transformant lines of the T4 progeny, which showed a large decrease in the transcript level of the TPT were used for further biochemical and physiological characterisation. In all antisense lines tested, TPT transport activity was diminished by 50-70% compared with the wild type (WT). Despite this high reduction in the transport capacity, alpha TPT plants la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 34 publications
6
72
1
2
Order By: Relevance
“…40 Surprisingly, plants with reduced levels of TPT have no substantial growth phenotype or reduction in photosynthetic capacity when grown under ambient conditions. [41][42][43][44][45][46] Such plants do, however, exhibit increased rates of starch turnover and export of neutral sugars to compensate for the defect in carbon allocation, which suggests that redundant or compensatory mechanisms also exist for the coupled defect in Pi import. PHT4;4 and PHT2;1 are candidates for this activity.…”
Section: Methodsmentioning
confidence: 99%
“…40 Surprisingly, plants with reduced levels of TPT have no substantial growth phenotype or reduction in photosynthetic capacity when grown under ambient conditions. [41][42][43][44][45][46] Such plants do, however, exhibit increased rates of starch turnover and export of neutral sugars to compensate for the defect in carbon allocation, which suggests that redundant or compensatory mechanisms also exist for the coupled defect in Pi import. PHT4;4 and PHT2;1 are candidates for this activity.…”
Section: Methodsmentioning
confidence: 99%
“…TPT is the major transporter in photosynthetic plastids as carbon fluxes, and it affects the rates of intraplastid starch biosynthesis and mobilization, and sucrose biosynthesis in the cytosol. 19,20) PK is a key regulatory enzyme in glycolysis, and is usually regulated under stressful conditions. [21][22][23] However, most studies have reported only a few genes for one or two metabolic reactions, which fails to explain the overall landscape of carbohydrate metabolic flows in plants.…”
Section: Detection Of Sugar Accumulation and Expression Levels Of Cormentioning
confidence: 99%
“…The simplifying assumption that leaf starch degradation is low or absent during the light period is supported by pulse-chase experiments with 14 CO 2 , which failed to detect significant starch degradation in standard light periods in pea (Pisum sativum; Kruger et al, 1983), pepper (Capsicum annuum; Grange, 1984), wild-type Arabidopsis (Arabidopsis thaliana; Walters et al, 2004;Zeeman et al, 2002), and tobacco (Nicotiana tabacum; Häusler et al, 1998) leaves (limitations of this approach are discussed in Supplemental Text S1). However, starch degradation may occur during long periods in continuous light, in some mutants with chloroplast export deficiencies, and in response to acute abiotic stress.…”
mentioning
confidence: 99%
“…Arabidopsis mutants with deficiencies in starch degradation accumulate higher levels of starch in constant light than wild-type plants, implying that starch levels in these conditions are determined by simultaneous synthesis and degradation (Caspar et al, 1991;Baslam et al, 2017). In triose phosphate transporter mutants of Arabidopsis and tobacco, the block in export of carbon from the chloroplast in the light is bypassed through starch turnover and export of starch degradation products (Häusler et al, 1998;Walters et al, 2004). Imposition of strong osmotic stress or photorespiratory conditions (zero CO 2 and elevated O 2 ) also rapidly induces starch degradation in the light during normal photoperiods (Weise et al, 2006;Thalmann et al, 2016).…”
mentioning
confidence: 99%